RNA helicase-dependent gene looping impacts messenger RNA processing. Issue 16 (30th August 2022) - Terrone, Sophie; Valat, Jessica; Fontrodona, Nicolas; Giraud, Guillaume; Claude, Jean-Baptiste; Combe, Emmanuel; Lapendry, Audrey; Polvèche, Hélène; Ameur, Lamya Ben; Duvermy, Arnaud; Modolo, Laurent; Bernard, Pascal; et al.
Abstract: DDX5 and DDX17 are DEAD-box RNA helicase paralogs which regulate several aspects of gene expression, especially transcription and splicing, through incompletely understood mechanisms. A transcriptome analysis of DDX5/DDX17-depleted human cells confirmed the large impact of these RNA helicases on splicing and revealed a widespread deregulation of 3′ end processing. In silico analyses and experiments in cultured cells showed the binding and functional contribution of the genome organizing factor CTCF to chromatin sites at or near a subset of DDX5/DDX17-dependent exons that are characterized by a high GC content and a high density of RNA Polymerase II. We propose the existence of an RNA helicase-dependent relationship between CTCF and the dynamics of transcription across DNA and/or RNA structured regions, that contributes to the processing of internal and terminal exons. Moreover, local DDX5/DDX17-dependent chromatin loops spatially connect RNA helicase-regulated exons with their cognate promoter, and we provide the first direct evidence that de novo gene looping modifies alternative splicing and polyadenylation. Overall our findings uncover the impact of DDX5/DDX17-dependent chromatin folding on pre-messenger RNA processing.